Invertebrate zoology - Ruppert, Edward E. 4 0 16; Barnes, Robert D.; 5 (Fort Worth : Saunders College Publishing, 1994)
A study of invertebrate zoology, examining a wide range of animal forms and functions, with a focus on the concepts that unify animal diversity.
Rev. ed. of: Invertebrate zoology / Robert D. Barnes. 5th ed. 1987.
Includes bibliographical references and index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Invertebrates. -- 20; 20; 2